Relationship Between Environmental Sanitation and Dengue Hemorrhagic Fever Incidents - Rafael Rodríguez Cortés; Weerapong Thanjangreed; Taisia Chertenko (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: The purpose of this study was to analyze the relationship between environmental sanitation and the incidence of Dengue Hemorrhagic Fever in the Unidad de Salud Work Area. Methodology: The study employed an analytical design using a survey method with a retrospective case-control approach. A total of 50 respondents were purposively sampled, comprising 25 Dengue Hemorrhagic Fever patients and 25 neighbors within ±10 meters who had no history of Dengue Hemorrhagic Fever. Data collection utilized a validated questionnaire (Cronbach's α = 0.803) focusing on environmental sanitation and vector control practices. Data analysis included univariate analysis for descriptive statistics and bivariate analysis using the chi-square test at a 95% confidence level to determine significant associations between risk factors and Dengue Hemorrhagic Fever incidence. Main Findings: The results of the study showed that there was a significant relationship between the independent variables, namely there was a relationship between house conditions and the incidence of Dengue Hemorrhagic Fever (p-value = 0.023), there was a relationship between water reservoir conditions and the incidence of Dengue Hemorrhagic Fever (p-value = 0.010), and there was a relationship between the waste disposal system and the incidence of Dengue Hemorrhagic Fever (p-value = 0.005) in the Unidad de Salud Work Area. Novelty/Originality of this study: This study offers a comprehensive approach to identify significant environmental determinants in influencing dengue incidence, which can form the basis for developing community-based interventions to improve the effectiveness of vector control.